Study protocol of a multicentre randomised controlled trial of self-help cognitive behaviour therapy for working women with menopausal symptoms (MENOS@Work) - Hunter, Myra S.; Hardy, Claire; Norton, Sam; Griffiths, Amanda (Elsevier, 2016)
Background